2017
DOI: 10.1175/jcli-d-17-0068.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Tropical Cyclone Activity and Structure to Global Warming in a High-Resolution Global Nonhydrostatic Model

Abstract: Future changes in tropical cyclone (TC) activity and structure are investigated using the outputs of a 14-km mesh climate simulation. A set of 30-yr simulations was performed under present-day and warmer climate conditions using a nonhydrostatic icosahedral atmospheric model with explicitly calculated convection. The model projected that the global frequency of TCs is reduced by 22.7%, the ratio of intense TCs is increased by 6.6%, and the precipitation rate within 100 km of the TC center increased by 11.8% un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(126 citation statements)
references
References 77 publications
8
114
3
1
Order By: Relevance
“…Both SST and OHC are projected to increase in the future (IPCC, ); there will be a warmer and wetter world over oceans and more energy available for evaporation (Emanuel, ; Trenberth & Fasullo, ; USGCRP, ; Yamada et al, ), facilitating more TC activity and more rainfall (Emanuel, ; Knutson et al, , ; Knutti & Sedláček, ; Vecchi & Soden, ; Walsh et al, ; Yamada et al, ). The question is whether the atmospheric conditions, in particular its stability and wind shear, also remain favorable, but these are likely at least episodically because convection plays a major role in stabilizing the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Both SST and OHC are projected to increase in the future (IPCC, ); there will be a warmer and wetter world over oceans and more energy available for evaporation (Emanuel, ; Trenberth & Fasullo, ; USGCRP, ; Yamada et al, ), facilitating more TC activity and more rainfall (Emanuel, ; Knutson et al, , ; Knutti & Sedláček, ; Vecchi & Soden, ; Walsh et al, ; Yamada et al, ). The question is whether the atmospheric conditions, in particular its stability and wind shear, also remain favorable, but these are likely at least episodically because convection plays a major role in stabilizing the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Kodama et al (2015) used this model with 14-km mesh to conduct climate simulations. Its outputs showed that the number of simulated ITCs matched the observational data (Satoh et al, , 2018Yamada et al, 2017). NICAM was utilized for investigating a relationship between TC genesis and intraseasonal oscillations Satoh et al, 2012;Taniguchi et al, 2010).…”
Section: Supporting Informationmentioning
confidence: 99%
“…As model resolution increases, stochastic approaches will become more valuable, as representing the interaction of the resolved scales with the subgrid through purely deterministic schemes becomes harder to justify (Dorrestijn et al 2013). 2) Global cloud-system-resolving models are a particularly important tool for understanding multiscale structures, such as the large-scale and synoptic environment of tropical cyclogenesis Yamada et al 2017) or largescale sea breezes and convection initiation (Birch et al 2015). They also demonstrate the potential of models in complementing and enhancing observations, for example, the discovery by Miyakawa et al (2012) of the three-fold structure of convective momentum transport associated with the Madden-Julian oscillation (MJO), using the high-resolution data by Miura et al (2007).…”
Section: Future Prospects and Challengesmentioning
confidence: 99%